Herta Müller en el exilio, la garra en el corazón: Herta Müller in exile, the claw in the heart - Carvajal Arguelles, Ines (Swedish Journal of Romanian Studies, 2023)
This article aims to show that Herta Müller's life is depicted as one of perpetual uprooting and to portrait elements in her novels where the writer deals with major universal themes, connected to the topic of exile and fundamental to understanding the turbulent 20th century in Europe. Her denunciation of the horrors of totalitarianism, against which she opposes a cry for freedom and against oblivion, stands out for its capacity for reflection, its originality and its poetic sensitivity, in such a way that it manages to traverse this arid terrain with original images of great beauty.